Recent Study on Wireless Body-Area Monitoring Network for Outdoor Environment - Al-Asadi, Ahmed Mohammed Q.; Wadday, Ahmed Ghanim (Advanced Aspects of Engineering Research Vol. 13, 2021)
Energy efficiency is a key issue for outdoor Wireless Body Area Networks (WBANs) that wireless sensor operates near or in the human body. WBAN suffered from a major problem of energy consumption. As a result, in outdoor simulation based on ZigBee S1 pro-type used as transmit and receiver model. The investigation has been carried out based on channel propagation characteristics of what used in simulation-based on ZigBee network with multiple sensing nodes, and the design can calculate the channel characteristic such as received power, path loss, path loss-free space, and path gain. The simulation enables to choose the best route to reduce energy consumption depending on the values that have been obtained. Simulation has two routes to using a multi-point route to transmit the data from patient nodes to the hospital. The power of the transmitter can be significantly reduced and effectively by using the method proposed, the method can effectively reduce the energy needed for sending the data.